Perlindungan Hukum Nasabah Perbankan dalam Perspektif Hukum Pidana di Indonesia - Sacra Resti Wulandari; Hafrida Hafrida; Erwin Erwin (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Legal protection for banking customers from a criminal law perspective has become a crucial issue in line with the increasing complexity of banking crimes, particularly those involving information technology. This study aims to analyze the current criminal law policy on the legal protection of banking customers in Indonesia (ius constitutum) and to formulate future policy directions (ius constituendum). The research employs a normative legal method using statutory, conceptual, case, and comparative approaches. Legal materials are analyzed through interpretation, evaluation, and assessment of various regulations, including Law Number 10 of 1998 concerning Banking, Law Number 8 of 1999 concerning Consumer Protection, the Law on Electronic Information and Transactions, as well as several regulations issued by the Financial Services Authority and Bank Indonesia. The results indicate that, normatively, Indonesia has established a relatively comprehensive legal framework to provide protection for banking customers through both preventive and repressive mechanisms. Preventive protection is implemented through supervision, the prudential principle, and the deposit insurance system, while repressive protection is carried out through criminal sanctions, civil claims, and dispute resolution mechanisms. However, the implementation of such protection still faces several challenges, including weak inter-agency coordination, the complexity of proving cybercrimes, and the unequal bargaining position between banks and customers. Therefore, criminal law reform oriented toward policy and value-based approaches is necessary, including regulatory strengthening, enhancement of law enforcement capacity, harmonization of regulations, and the application of a more progressive liability principle for banks. Through this integrative approach, criminal law protection for banking customers is expected to become more effective, adaptive, and just.